The effects of the size of a boiling bubble on lesion production in boiling histotripsy - Pahk, K. J.; de Andrade, M. O.; Kim, H.; Saffari, N. (17TH ANNUAL ANGLO-FRENCH PHYSICAL ACOUSTICS CONFERENCE (AFPAC), 2019)
Boiling histotripsy employs a number of millisecond-long High Intensity Focused Ultrasound (HIFU) pulses with high acoustic peak pressures at the HIFU focus to mechanically fractionate soft tissue. Studies have shown the mechanisms underpinning this tissue fractionation process; however, the question of how HIFU exposure conditions affect lesion formation still remains unclear. In the present work, a high-speed camera and a passive cavitation detection (PCD) system were used to investigate the dynamics of bubbles induced and the corresponding mechanical damage generated in optically transparent tissue-mimicking phantoms with two different boiling histotripsy exposure conditions (1. P+ = 85.4 MPa, P- = - 15.6 MPa; 2. P+ = 71.5 MPa, P- = - 13.4 MPa at focus). Our results clearly showed that there is a positive relationship between the size of a boiling bubble and the lesion dimension. At P+ = 85.4 MPa and P- = - 15.6 MPa, a relatively larger boiling bubble was, for instance, produced at the focus in the gel phantom followed by the presence of a wider cavitation cluster progressing toward the HIFU transducer, resulting in the formation of a larger lesion compared to that with P+ = 71.5 MPa and P- = - 13.4 MPa.